Arabic Language Teachers' Beliefs about Listening in Relation to their Practice of Listening Comprehension Teaching Strategies - Hawamdeh, Mohammad F. (Dirasat: Educational Sciences, 2024)
Objectives: The study aims to uncover the beliefs of Arabic language teachers regarding listening and explore the potential correlational relationship, if any, between teachers' beliefs about listening and their practices in teaching listening comprehension strategies. Methods: To achieve the study's objectives, the researcher developed a scale for measuring Arabic language teachers' beliefs about listening, consisting of 23 items. Additionally, a scale for assessing Arabic language teachers' practices of listening comprehension teaching strategies, developed by Al-Khawaldeh and Al-Hawamdeh (2016), was used. This scale consists of 20 items distributed across three areas: pre-listening, during listening, and post-listening. Both scales were validated for reliability and validity. The study sample consisted of 77 teachers from the Irbid District Directorate of Education, selected through simple random sampling during the first semester of the 2023/2024 academic year. Results: The study's results showed that the beliefs of Arabic language teachers about listening, as measured by the scale, were generally high. The results also indicated that the teachers' self-assessment of their practices in teaching listening comprehension strategies was high. Furthermore, a statistically significant positive relationship was found between the teachers' beliefs about listening and their self-assessment of their practices in teaching listening comprehension strategies. Conclusions: This study provided scientific evidence of the relationship between Arabic language teachers' beliefs and their practices in teaching listening skills, as well as the impact of these beliefs on their teaching practices.